The Effects of FDM Printing Parameters on the Compression Properties of Polymethylmethacrylate (PMMA) using Finite Element Analysis - Sukindar, Nor Aiman; Mohd Samsudin, Noorazizi; Syed Shaharuddin, Sharifah Imihezri; Kamaruddin, Shafie (International Journal of Integrated Engineering, 2022)
3D printing technology has become a favored alternative in fabricating parts due to its flexibility in product customization. Recently, an abundant number of studies have been conducted to improve the overall quality of the 3D printed parts. One of the essential qualities is to provide mechanical properties that fulfill the functionality of the final product. Thus, providing the best option in tailoring the mechanical properties of 3D printed parts is very useful. This paper investigates the effects of printing parameters on the mechanical properties of Polymethylmethacrylate (PMMA) using finite element analysis (FEA). Taguchi’s 33 design-of-experiment methods were used to design the experiment for the following printing parameters: shell thickness, type of infill, and infill density. The compressive test was performed using Ansys software and the variables under study were strain and total deformation. The results obtained from the FEA simulation show that the strain and total deformation are mainly influenced by infill density, followed by the type of infill and shell thickness. It is deduced from the study that the optimum printing parameters with higher infill density (70%) and combination with triangular infill pattern able to hold the structure more rigidly, therefore providing more resistance against deformation. This study proposed a platform for determining the mechanical properties of 3D models for FDM printed parts using FEA analysis.